DEVELOPMENT OF CHARISMATIC KIAI LEADERSHIP IN ISLAMIC BOARDING SCHOOLS FACING THE CHALLENGES OF MODERNIZATION Case Study in Al-Islamiyyah Islamic Boarding School Cikalong Wetan West Bandung - Ambya, Rachanda; Nuryadin, Riyan; Purnama, Wawan; Sugiana, Yusuf; Arifin, Bambang Samsul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic boarding schools as traditional Islamic educational institutions have a strategic role in shaping the character of the young generation through the instillation of religious values, with the kiai as a central figure who plays a role as an educator and charismatic spiritual leader who influences the lives of students and the surrounding community. However, during the development of the era and the influence of modernization, the role of charismatic kiai faces new challenges that require adjustments in relevant leadership methods. This study aims to understand the characteristics of charismatic kiai leadership in Islamic boarding schools, identify factors that support the development of this leadership, and explore the strategies implemented by kiai in facing the challenges of modernizing Islamic boarding schools. The research method uses a qualitative approach with a case study method at the Al-Islamiyah Islamic Boarding School, West Bandung Regency. Data were collected through direct observation, documentation studies, and in-depth interviews with kiai, staff, and students. The results of the study show that the characteristics of charismatic kiai leadership include exemplary behavior, simplicity, devotion to worship, humility, caring, wisdom, and persuasion. Factors that support the development of this leadership include collaboration and active involvement, open communication, development of professionalism, and adaptation to technology. The implementation of these findings includes strategies implemented by the kiai, namely the involvement of all parties in decision-making, integration of traditional values with modernity, encouraging innovation and critical thinking, strengthening networks and cooperation, and emphasizing morals and character. In conclusion, charismatic kiai leadership plays a crucial role in leading Islamic boarding schools to remain relevant and advanced in the modern era without abandoning the identity and fundamental values of the Islamic boarding school. This study fills the gap in previous literature that has not studied much about the development of charismatic kiai leadership in the